2017
DOI: 10.3390/ijgi6110320
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variability in a Turbid and Dynamic Tidal Estuarine Environment (Tasmania, Australia): An Assessment of MODIS Band 1 Reflectance

Abstract: Patterns of turbidity in estuarine environments are linked to hydrodynamic processes. However, the linkage between patterns and processes remains poorly resolved due to the scarcity of data needed to resolve fine scale highly dynamic processes in tidal estuaries. The application of remote sensing technology to monitor dynamic coastal areas such as estuaries offers important advantages in this regard, by providing synoptic maps of larger, constantly changing regions over consistent periods. In situ turbidity me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Inland, coastal and estuarian shallow water area is dependent on the dynamics of sediments originated by wave erosion, tidal currents, hydrological parameters, biological and chemical constituent of water. For that this region presents a complex optical proprieties of case 2 waters, they are influenced by turbidity TU, Total suspended sediments TSS, dissolved matter, organic matter, microorganism, inorganic particulates matter from minerals [21].…”
mentioning
confidence: 99%
“…Inland, coastal and estuarian shallow water area is dependent on the dynamics of sediments originated by wave erosion, tidal currents, hydrological parameters, biological and chemical constituent of water. For that this region presents a complex optical proprieties of case 2 waters, they are influenced by turbidity TU, Total suspended sediments TSS, dissolved matter, organic matter, microorganism, inorganic particulates matter from minerals [21].…”
mentioning
confidence: 99%
“…Generally, the water reflectance in the red part of the spectra is well correlated to the light backscattering by suspended sediments in the water column for low to moderate sediment concentrations [43]. Previous studies have demonstrated that RS atmospheric correction algorithms are successfully applied to highly turbid waters [44][45][46][47]. However, this has not been tested with Landsat imagery yet.…”
mentioning
confidence: 99%
“…For images covered by clouds, the methodology based on band 2 was applied to remove cloud contamination [2,3,12]. Many studies have tested this product and the reflectance was found to have significant correlation with in situ turbidity measurements and SSC in coastal areas [1,12,23,24].…”
Section: Modis Datamentioning
confidence: 99%
“…Many studies have developed algorithms to retrieve SSC and turbidity, using the correlation between in situ observations and the reflectance measurements obtained by MODIS and other ocean color sensors [1,11,23,31]. The algorithm used for this study is based on the semi-analytic sediment model (SASM), which was applied to MODIS-Aqua observations by Dorji et al [32].…”
Section: Turbidity Retrieval Algorithmmentioning
confidence: 99%